2022
DOI: 10.3390/jcm11133905
|View full text |Cite
|
Sign up to set email alerts
|

How Does Vaccination against SARS-CoV-2 Affect Hospitalized Patients with COVID-19?

Abstract: (1) Background: The development of effective COVID-19 vaccines has reduced the impact of COVID-19 on the general population. Our study aims to analyze how vaccination modifies the likelihood of death and length of stay in hospitalized patients with COVID-19; (2) Methods: A retrospective cohort study of 1927 hospitalized patients infected with COVID-19 was conducted. Information was gathered on vaccination status, hospitalization episode, and clinical profile of the patients. The effect of vaccination on mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The findings of the present study showed that the mortality rate in patients hospitalized in the care units for Corona patients decreased after the start of general vaccination for COVID-19. The results of the study by R. Kempker et al (2022) [ 36 ] and the results of the study by P. Moreno-Nunez et al (2022) [ 37 ] are in line with this finding of the present study. The results of their study showed that the start of general vaccination for COVID-19 was associated with a decrease in mortality in patients hospitalized in COVID-19 wards.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study showed that the mortality rate in patients hospitalized in the care units for Corona patients decreased after the start of general vaccination for COVID-19. The results of the study by R. Kempker et al (2022) [ 36 ] and the results of the study by P. Moreno-Nunez et al (2022) [ 37 ] are in line with this finding of the present study. The results of their study showed that the start of general vaccination for COVID-19 was associated with a decrease in mortality in patients hospitalized in COVID-19 wards.…”
Section: Discussionsupporting
confidence: 92%